2020
DOI: 10.3390/ijerph17197011
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Colic—The Perspective of German and Polish Pediatricians in 2020

Abstract: The objective of the study was to characterize how infantile colic is perceived and managed by German and Polish pediatricians. Data in both countries were collected by using a paper questionnaire with seven questions and predefined and free text fields for the answers. Answers from 160 German and 133 Polish pediatricians were collected. The average of the occurrence rates estimated by both responder groups were at the higher end of published rates. The majority of pediatricians from both countries rated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…Present survey study also found out that medical treatments were prescribed by the vast majority of the physicians and previous treatment outcome experience was the most important single determinant on their treatment preference. Similar to the present study, surveys conducted in Europe have also shown that the majority of physicians establish the diagnosis based on clinical experience alone ( 14 , 15 ).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Present survey study also found out that medical treatments were prescribed by the vast majority of the physicians and previous treatment outcome experience was the most important single determinant on their treatment preference. Similar to the present study, surveys conducted in Europe have also shown that the majority of physicians establish the diagnosis based on clinical experience alone ( 14 , 15 ).…”
Section: Discussionsupporting
confidence: 86%
“…The lowest prevalence rates were reported from Denmark (6%) and Japan (2%) among infants up to 6 weeks of age, while the highest prevalence rates (17–47%) were reported from the UK in infants of 1–2 weeks of age ( 2 ). In a survey among German and Polish paediatricians, the proportion of infants diagnosed with IC was 41.6% for the German paediatricians, while this figure was 38% in another survey from Australia ( 14 , 15 ). In the current study where all participants were paediatricians, IC diagnosis was most commonly reported in infants of 4–6 weeks of age, followed by those aged 2–4 weeks.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations